Managing nuclear projects : a comprehensive management resource - Devgun, Jas (Woodhead Publishing in energy, 2013)
In addition to the nuclear power industry, the nuclear field has extensive projects and activities in the areas of research reactors, medical isotope production, decommissioning, and remediation of contaminated sites. Managing nuclear projects focuses on the management aspects of nuclear projects in a wide range of areas with emphasis on process, requirements, and lessons learned. Part one provides a general overview of the nuclear industry including basic principles for managing nuclear projects, nuclear safety culture, management of worker risk, training, and management of complex projects. Part two focuses on managing reactor projects with discussion on a variety of topics including management of research reactor projects, medical radioisotope production, power reactor modifications, power uprates, outage management, and management of nuclear-related R & D. Chapters in part three highlight the areas of radioactive waste and spent fuel management, reactor decommissioning, and remediation of radioactively contaminated sites. Finally, part four explores regulation, guidance and emergency management in the nuclear industry. Chapters discuss quality assurance and auditing programs, licensing procedures for nuclear installations, emergency preparedness, management of nuclear crises, and international nuclear cooperation. With its distinguished editor and contributors, Managing Nuclear Projects is a valuable resource for project managers, plant managers, engineers, regulators, training professionals, consultants, and academics. Examines the basic principles of managing nuclear projects focussing on processes and requirementsDiscusses the management of reactor projectsExplores regulation, guidance and emergency management in the nuclear industry.